Transformasi Akad: Peran Platform E-Commerce dalam Menjembatani Perdebatan Shighat dan Mitigasi Gharar pada Jual Beli Kontemporer - Hakim, Luqman; Al Yamani, Jalaluddin; Salsabila, Tasya (Fakultas Syariah UIN Prof. K.H. Saifuddin Zuhri, 2025)
The digital revolution has fundamentally transformed commercial transactions, giving rise to practices such as pre-orders in e-commerce. This study examines how contemporary e-commerce platforms not only transform the classic Bai' as-Salam contract but also address the classical jurisprudence （fiqh debate regarding the validity of the contract form （shighat. Traditionally, schools of fiqh （such as Hanafi and Syafi'i） have differed on the validity of non-verbal contracts （mu'athah） due to potential uncertainty （gharar. This article argues that modern e-commerce platforms function as a